Retention or defection? Chinese consumers' decision-making styles for domestic and global brands - S. Y. Tzeng; W. M. Wong (South African Journal of Business Management, 2016)
This study explores consumers' decision-making in terms of intention to switch to foreign brands from domestic brands when purchasing cell phones and sports shoes. A survey of 584 undergraduates in Guangdong, China, shows that domestic brands retain their low quality-conscious, low fashion-and-recreational-conscious and low price-conscious customers and attract low brand-conscious and high choice-confused buyers from foreign brands. Foreign brands typically retain their consumers who are highly conscious of fashion and recreation and keep and draw customers with low choice confusion. High-price-conscious consumers and those who are highly brand-confused will assess foreign and domestic brands when searching for bargains. Regarding managerial implications, local brands should offer products of high quality at low pricesand constantly invest in R D; foreign brands may expand their customer bases and build interactive brand channels; all companies can retain brand-confused customers with preferential packages and design their marketing strategies based on decision-making styles of their target consumers.
Keywords: 650